Regional gray matter thickness correlations of the hearing and deaf feline brains - Stephen G. Gordon; Alessandra Sacco; Stephen G. Lomber (NeuroImage: Reports)
The overall function and associated structure of the brain changes dramatically following early-onset hearing loss in a process known as compensatory crossmodal plasticity. As the microscale changes to cerebral morphology driving these adaptations can be reflected macrostructurally in MRI analyses, high interregional correlations in features such as gray matter thickness are potentially indicative of functional relationships. To probe the changes in these associations following deafness using structure alone, perinatally-deafened and hearing control cats were scanned at 7T to obtain high-resolution T1-weighted images. After calculating regional thicknesses for 146 cortical areas, the 10,585 associated pairwise correlations were used to establish group-specific structural connectomes. Similar distributions of correlation strength were revealed between the two populations, however there was an overall increase in the density of the structurally-defined connectome following deafness. The connections demonstrating the most dramatic increases of correlational strength in the deprived group were those relating to the auditory and visual cortices, with a more balanced distribution of increases and decreases to connections involving solely non-sensory regions. In corroboration with previous feline structural- and diffusion-based neuroimaging literature, these results imply a reorganization of cortical gray matter to increase the overall processing of the remaining senses within a potentially less complex and more redundant connectome. The present study adds to the developing field of deafness literature through the implementation of novel analyses that add an additional perspective on neuroplasticity within the feline brain.